2011
DOI: 10.1111/j.1365-294x.2011.05239.x
|View full text |Cite
|
Sign up to set email alerts
|

ABGD, Automatic Barcode Gap Discovery for primary species delimitation

Abstract: Within uncharacterized groups, DNA barcodes, short DNA sequences that are present in a wide range of species, can be used to assign organisms into species. We propose an automatic procedure that sorts the sequences into hypothetical species based on the barcode gap, which can be observed whenever the divergence among organisms belonging to the same species is smaller than divergence among organisms from different species. We use a range of prior intraspecific divergence to infer from the data a model-based one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
2,317
4
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,692 publications
(2,366 citation statements)
references
References 67 publications
21
2,317
4
24
Order By: Relevance
“…The alignment was submitted to the Automatic Barcode Gap Discovery (ABGD) Server (http:// wwwabi.snv.jussieu.fr/public/abgd/) that calculates a barcode gap from the inference of a model-based one-sided confidence limit for intraspecific divergence (Puillandre et al 2012). Minimum prior intraspecific divergence (0·001) and maximum prior intraspecific divergence (0·1) were scanned over 10 steps with a minimum gap width (1·5) and distance distribution Nn bins (20).…”
Section: Bioinformatic Analysis Of the Coi Genementioning
confidence: 99%
“…The alignment was submitted to the Automatic Barcode Gap Discovery (ABGD) Server (http:// wwwabi.snv.jussieu.fr/public/abgd/) that calculates a barcode gap from the inference of a model-based one-sided confidence limit for intraspecific divergence (Puillandre et al 2012). Minimum prior intraspecific divergence (0·001) and maximum prior intraspecific divergence (0·1) were scanned over 10 steps with a minimum gap width (1·5) and distance distribution Nn bins (20).…”
Section: Bioinformatic Analysis Of the Coi Genementioning
confidence: 99%
“…These groups were considered to be equivalent to species (Puillandre et al, 2012). ABGD was used through its online tool (http://wwwabi.snv.jussieu.fr/ public/abgd/abgdweb.html) with default settings.…”
Section: Dna Taxonomymentioning
confidence: 99%
“…Alignment was done using the default settings and optimized manually when necessary. Initial identification was carried out using BLAST n searches in the NCBI and BOLD databases and then by using the "Automatic Barcode Gap Discovery Software" (PUILLANDRE et al, 2012) for identifying DNA barcodes. Interspecific pairwise distances between all species were calculated using Kimura's two-parameter (K2P) model (KIMURA,1980).…”
Section: Discussionmentioning
confidence: 99%
“…Identification using Automatic Barcode Gap Discovery (PUILLANDRE et al 2012) showed nine different groups that corresponded to species identified using BLAST n searches in the NCBI database, indicating the efficiency of DNA barcoding for species identification. NeighborJoining phylogenetic analysis, generated from K2P distances, showed that species are grouped according to the groups identified using Automatic Barcode Gap Discovery analysis (Figure 1).…”
Section: A Total Ofmentioning
confidence: 99%